Utilization of Agricultural Information Sources and Adoption of Animal and Crop Technologies Among Farming Households in Imo State, Nigeria - Chisom Norberth Uwandu; Kehinde Adesina Thomas; Chinwe Mercy Okoro (Journal of Agricultural Extension, 2018)
The study ascertained effect of utilization of agricultural information sources on adoption of animal and crop technologies among farming households in Imo State, Nigeria. Structured interview schedule was used to collect data from one hundred and fifty respondents using a multi-stage sampling technique. Data were analyzed using both descriptive and inferential statistics: PPMC and t test. Respondent’s mean age was 48 years; 99.1% had contact with extension agents; 88.4% had access to between 1 and 5 hectares of land; 33.6% practiced crop science; 29.9% practiced animal science. Recommended crop spacing was adopted by 36.6% of the respondents; while 29.9% adopted improved breeds of livestock. Agricultural Development Project (ADP) was the most accessed (x̅ = 2.97) information source. There was a significant relationship between use of agricultural information sources and adoption of crop technologies (r=0.262; p < 0.000), while significant difference (t=3.068; p < 0.05) existed in the adoption of crop technologies between respondents with low and high access to agricultural information. Efforts by relevant agencies to improve frequency of use of information sources relating to appropriate crop and animal technologies will ultimately increase their adoption of these technologies.